Field assessment of insecticide dusting and bait station treatment impact against rodent flea and house flea species in the Madagascar plague context - Miarinjara, Adélaïde; Rahelinirina, Soanandrasana; Razafimahatratra, Nadia Lova; Girod, Romain; Rajerison, Minoarisoa; Boyer, Sebastien (PLOS Neglected Tropical Diseases, 2019)
Author summary Insecticide ground dusting inside houses is the recommended measure to control rat fleas responsible for bubonic plague transmission. The main inconvenience of this method is the direct contact of houseowners to the toxic insecticide dust and spillage in environment. A bait station approach, where the insecticide is confined in a box or tunnel containing rodent attractant, seems to be a valuable complementary or alternative vector control tool. However currently, little is known about its real efficacy on reducing or eliminating fleas harbored by rats. Guidelines regarding its implementation (density and duration of use) as vector control tool are lacking. Those questions were addressed during a field trial study, where bait stations were deployed at different densities per household and followed up at different time points. The efficacy of bait station was compared to the standard method. The present study allowed to demonstrate that bait station approach requires more improvements to be efficient. Meanwhile, insecticide ground dusting is still recommended for to control rat fleas during epidemics.